Pengaruh Kemiskinan dan Pengangguran terhadap Indeks Pembangunan Manusia di Provinsi Jawa Barat - Rahmat Hidayat; Vemas Praditya Pangestu; Muhammad Al-Hafiz Ridwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article examines the impact of poverty and unemployment on the Human Development Index (HDI) in the West Java region. Poverty and unemployment are two key factors that play a role in reducing people's quality of life. This research utilizes secondary data from the Central Statistics Agency and other sources to analyze the relationship between poverty levels, unemployment levels and HDI developments in the region. The findings show that increasing poverty and unemployment have a significant negative effect on HDI, which includes health, education and income indicators. These results highlight the importance of comprehensive intervention policies to address the problems of poverty and unemployment in order to improve the quality of life and welfare of people in Indonesia.